Cardiovascular diseases and related risk factors accelerated cognitive deterioration in patients with late-life depression: a one-year prospective study. (October 2019) - Zhong, Xiaomei; Wu, Zhangying; Ouyang, Cong; Liang, Wanyuan; Chen, Ben; Peng, Qi; Mai, Naikeng; Wu, Yuejie; Chen, Xinru; Zhang, Min; Ning, Yuping
ABSTRACT: Objectives: Cognitive impairment in late-life depression is common and associated with a higher risk of all-cause dementia. Late-life depression patients with comorbid cardiovascular diseases (CVDs) or related risk factors may experience higher risks of cognitive deterioration in the short term. We aim to investigate the effect of CVDs and their related risk factors on the cognitive function of patients with late-life depression. Methods: A total of 148 participants were recruited (67 individuals with late-life depression and 81 normal controls). The presence of hypertension, coronary heart disease, diabetes mellitus, or hyperlipidemia was defined as the presence of comorbid CVDs or related risk factors. Global cognitive functions were assessed at baseline and after a one-year follow-up by the Mini-Mental State Examination (MMSE). Global cognitive deterioration was defined by the reliable change index (RCI) of the MMSE. Results: Late-life depression patients with CVDs or related risk factors were associated with 6.8 times higher risk of global cognitive deterioration than those without any of these comorbidities at a one-year follow-up. This result remained robust after adjusting for age, gender, and changes in the Hamilton Depression Rating Scale (HAMD) scores. Conclusions: This study suggests that late-life depression patients with comorbid CVDs or their related risk factors showed a higher risk of cognitive deterioration in the short-term (one-year follow up). Given that CVDs and their related risk factors are currently modifiable, active treatment of these comorbidities may delay rapid cognitive deterioration in patients with late-life depression.